Evaluation of Some Physical Charactistics of Bottled Drinking Water Samples Circulating in Sebha City-Libya - زيدان ضو اهويدي و مصطفي الأمين الصادق (Journal of Pure & Applied Sciences, 2020)
This study was conducted on some brands of bottled drinking water circulating in the local market of Sebha city. The study included 11 samples of locally produced and imported. A number of physical properties such as density, surface tension, viscosity, electrical conductivity, refractive index, turbidity and PH were evaluated. The results of physical parameters of the bottled water samples were compared with the values labeled in the bottles. Some of the parameters such as electrical conductivity, turbidity, are either not labeled at all or labeled only in few brands of bottled water. The turbidity results showed that 55% was totally free from plankton, and PH values ​​were within the limits permitted by World Health Organization (WHO). As for the surface tension values, they have increased significantly compared to the standard value of the surface tension of water. The results of the statistical analysis showed that there is a perfect positive correlation between the electrical conductivity and the total dissolved solids as well as a significant positive correlation between surface tension and density. According to the weighted arithmetic water quality index, 46% of the samples were in excellent water quality. In comparison to the specifications of bottled drinking water issued by the National Center for Standards and Metrology, the World Health Organization, and international bottled water association (IBWA) the brands of bottled drinking water produced locally in Libya and the imported brands included in this study achieved a good level of quality in all physical parameters.